2019
DOI: 10.1093/aob/mcz062
|View full text |Cite
|
Sign up to set email alerts
|

Alternative analyses of compensatory base changes in an ITS2 phylogeny of Corydalis (Papaveraceae)

Abstract: Background and Aims Compensatory base changes (CBCs) that occur in stems of ribosomal internal transcribed spacer 2 (ITS2) can have important phylogenetic implications because they are not expected to occur within a single species and also affect selection of appropriate DNA substitution models. These effects have been demonstrated when studying ancient lineages. Here we examine these effects to quantify their importance within a more recent lineage by using both DNA- and RNA-specific models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…Compensatory base change (CBC) or compensatory mutation, wherein a base substitution on one side (hemi-CBC) is compensated by a substitution on the other side of that base pair, is expected to restore base-pairing and maintain the structure [ 42 ]. From an evolutionary perspective, such CBCs can be reserved in an ancestral ITS2 structure and are inherited by its descendant, making structural states include unique phylogenetic information not found in the nucleotide sequence [ 43 ].…”
Section: Cbc In Its2 Secondary Structurementioning
confidence: 99%
See 3 more Smart Citations
“…Compensatory base change (CBC) or compensatory mutation, wherein a base substitution on one side (hemi-CBC) is compensated by a substitution on the other side of that base pair, is expected to restore base-pairing and maintain the structure [ 42 ]. From an evolutionary perspective, such CBCs can be reserved in an ancestral ITS2 structure and are inherited by its descendant, making structural states include unique phylogenetic information not found in the nucleotide sequence [ 43 ].…”
Section: Cbc In Its2 Secondary Structurementioning
confidence: 99%
“…Based on the above evidence, wherein CBCs occur between rather than within species, Wolf et al proposed a generalized “CBC species concept” [ 55 ]. Further development of Coleman’s hypothesis showed that CBC should expand to all four helices and even hemi-CBC rather than being restricted to helix II and III as Coleman originally suggested [ 43 , 56 , 57 ]. In practice, rapid identification of the ITS2 CBC among the potential parental species and assessing their fertility before their actual cross experiment could reduce the incompatible mating pairs and save time.…”
Section: Species Delimitation Based On Its2-cbcmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of CBCs can be the underlying reason that ITS2 has appeared to be an effective indicator of species identification, accumulating mutations in reproductively isolated populations [ 39 ]. Thus, it has been shown that determining the presence of CBCs in ITS2 rRNA secondary structures is a reliable diagnostic tool of taxon analysis in prokaryotes placozoans [ 40 ] as well as higher eukaryotic lineages such as tick Paramacrobiotus [ 41 ], Altica beetles [ 42 ] and flowering plant Corydalis [ 43 ]. Furthermore, CBC analysis has been shown to play a supportive role in uncovering cryptic species in taxa including the marine protist Amoebophrya ceratii [ 44 ], marine diatom genus Pseudo-nitzschia [ 45 ] and skipper butterfly Urbanus belli [ 46 ].…”
Section: Introductionmentioning
confidence: 99%